Pembuatan Aplikasi Catalog 3D Desain Rumah Sebagai Sarana Promosi Dengan Menggunakan Unity 3D - Adnin, Siryantini Nurul; Widiartha, Ida Bagus Ketut; Suksmadana, I Made Budi (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 7, No. 1 April 2016DO - 10.24843/LKJITI.2016.v07.i01.p01, 2016)
T his study incorporate AR into a technology home Catalog sales, thus Catalog home is becoming more real with 3D objects in it. This research aims to produce an application that can display a 3D model of a house that can help buyers to know well the home to be purchased, and will simplify the home seller as a media campaign to consumers. 3D objects used to develop two kinds of Software that Sweet Home 3D and Blender, whereas to create application in programming used Unity 3D Software using the C # programming language. Application home design Catalog is made through several stages of design 3D objects, Marker workmanship and application design. The end result consists of two forms, namely in the form of physical (in the form of print media Catalog) that contains a marker on some pages and Augmented Reality applications based on Android in the form of .apk which is then installed on Smartphones, where the two are complementary.
Keywords: Augmented Reality, Unity, Marker, C#, Catalog.